TRAINING ON EXPERTISE OF DESIGNING GRAPHIC DESIGN PROGRAM IN CLAY PHOTO AND CINEMA - Halim, Bobby; Viatra, Aji Windu (Batoboh, 2019)
The training to improve the expertise in designing graphic design by utilizing Adobe Photoshop, Illustrator and Premiere programs aims to provide skills in making attractive graphic designs. The mastery of the ability to design electronic advertising media with social media applications (social media) controlled by human resources graphic design programs by graphic designers is expected to spark interest in more eager to develop capabilities, and ultimately improve the quality of overall digital graphic design. The method applied in this activity is the method of presentation regarding the introduction of software, its usefulness, and its application in making interactive learning media, the workshop / demonstration method regarding the operationalization of the program and the practical method of making technical tips and tricks directly for participants in accordance with their respective sub-work each with the use of Adobe programs. Evaluation method by observing differences in the ability of designers before and after training. The results achieved an increase in creative and artistic abilities. Evaluation of the results seen from the assessment of practical tasks that illustrate the success of the material that has been presented. Besides that, the participants' performance and participation were observed.